The Role of p16, p21, p27, p53 and Ki-67 Expression in the Differential Diagnosis of Cutaneous Squamous Cell Carcinomas and Keratoacanthomas: An Immunohistochemical Study - (:unkn) unknown (My University, 2016)
0

Background: Distinguishing squamous cell carcinoma (SCC) from keratoacanthoma (KA) by histopathological features may not be sufficient for a differential diagnosis, as KAs may, in some cases, imitate well-differentiated SCCs. Aims: In this study, we investigated whether the expression of the p16, p21, p27, p53 genes and a Ki-67 proliferation index are useful in distinguishing between these two tumors. Study Design: Cross-sectional study. Methods: Immunohistochemistry was used to investigate the expression of the p16, p21, p27, p53 genes and the Ki-67 proliferation index was investigated in well-differentiated SCC with KA-like features (n=40) and KA (n=30). Results: The results of all of the examined markers, except for p27 (p16, p21, p53, and Ki-67) were found to be significantly different between the SCC and KA samples (p<0.05). Conclusion: In well-differentiated SCC with KA-like features and KA cases where the differential diagnosis is difficult from a histopathological perspective, the use of p16, p21, p53 expression and a Ki-67 proliferation index can be useful for the differential diagnosis of SCCs and KAs.
Keywords: Cerrahi